Ecological Footprints for Aquaculture Possibility in Selected Mangrove Regions of Jaffna, Sri Lanka - Saruga, S.; Sivashanthini, K.; Sutharshiny, S.; Gunaalan, K.; Shobiya, P. (University of Jaffna, 2019)
The present study was carried out to analyze the possibility of practicing aquaculture in selected mangrove regions in Jaffna, Sri Lanka. A detailed study on the possibility of undertaking aquaculture has been carried out in Sarasaalai and Kapputhu mangrove regions. The water quality parameters were measured, organic matter was estimated and available fish species were collected and identified during the study period. Samples were collected in the second week of each month from June 2016 to November 2016. Water quality parameters such as water temperature, salinity, pH, dissolved oxygen, water depth and turbidity were measured. Organic matter was estimated for soil samples collected from the study areas. Water quality parameters were analyzed by two sample t-test using minitab13. Identification of all collected fish species were confirmed according to the standard literature by observing their morphological and meristic characters. Statistical analysis shows no significant difference between Sarasaalai and Kapputhu in water temperature (P =0.062), salinity (P = 0.402), dissolved oxygen (P = 0.773), pH (P = 0.262) and water depth (P =0.798). Significant difference (P = 0.001) was observed for turbidity in both locations. High percentage of organic matter was observed in Sarasaalai. The identified fish species in both locations were Chanos chanos, Platycephalus fuscus, Oreochromis mossambicus, Nematalosa nasus, Hyporhamphus limbatus, Hemiramphus marginatus, Etroplus maculatus, Gerres abbreviatus and Gerres oyena. The most abundant species found in Sarasaalai was O. mossambicus and in Kapputhu were O. mossambicus, C. chanos, G. abbreviatus and G. oyena. The present investigation inferred that the specified species can be cultured in the said regions. However, a long term study on seed resources, environmental and climatic conditions of particular site would ensure more details on culture aspects of these species.
Keywords: Aquaculture; C. chanos; G. abbreviatus; Mangrove; O. mossambicus